HALLYU SEBAGAI FENOMENA TRANSNASIONAL - Indah Chartika Sari; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
In recent years, Republic of Korea‟s (ROK) cultural industry attracted more half of world by unique and peace culture. It known as Hallyu or Korean Wave which has entertained international public with several cultural contents like; television drama (K-Drama), film, music (K-Pop), fashion (K-Fashion), etc. In 2010 ROK‟s government apply new cultural policy to spreading Hallyu all over the world, like; High Speed Internet Service Program. This policy used social media as instrument to spreading cultural contents. Hallyu became transnational phenomenon because it successfully attracted international public as good influence for world cultural development. This research focuses about Hallyu as local culture became successful as transnational phenomenon including the actors, mass media and spreading strategy. The actors refers to government, chaebol, idol grouped whose involve into public diplomacy to promote Hallyu. Mass media as instrument to promote Hallyu in creative ways by K-Drama, K-Pop, cartoon and many others. Spreading strategy refers to how actors and mass media as an instrument to create mind and though of international public about Hallyu as positive influence which bring peace missions by attractive culture. In other hand, ROK‟s government has succeed to promote local culture to the world in creative and attractive ways.Keywords: Cultural Diplomacy, Hallyu, Popular Culture, Public Diplomacy.